Evaluation of mercury methylation and methylmercury demethylation rates in vegetated and non-vegetated saltmarsh sediments from two Portuguese estuaries. (July 2017) - Cesário, Rute; Hintelmann, Holger; Mendes, Ricardo; Eckey, Kevin; Dimock, Brian; Araújo, Beatriz; Mota, Ana Maria; Canário, João
Abstract: Neurotoxic methylmercury (MMHg) is formed from inorganic divalent mercury (Hg 2+ ). However, it is poorly understood to what extent different mercury (Hg) pools contribute to existent MMHg levels. In this study, ambient concentrations of total Hg (THg) and MMHg as well as rates of methylation and demethylation were measured simultaneously in sediments with and without salt-marsh plant vegetation, which were collected in Guadiana and Tagus estuaries, Portugal. Concurrent processes of Hg methylation and MMHg demethylation were directly monitored and compared by spiking sediments cores with stable isotope tracers of 199 Hg 2+ and CH3 201 Hg + followed by gas chromatographic separation and isotope-specific detection using inductively coupled plasma mass spectrometry. Compared to the Guadiana estuary, where concentrations were comparatively low, THg and MMHg levels varied between vegetated and non-vegetated sediments collected at the Rosário site (ROS) of the Tagus estuary. Methylation (KM ) and demethylation rates (KD ) were also different between estuaries being dependent on the presence of vegetation. In addition, the type of macrophyte species influenced KM and KD values. In fact, the highest KM value was found in Sarcocornia fruticosa vegetated sediments at the Castro Marim site in Guadiana (CM, 0.160 day −1 ) and the lowest KM was observed in non-vegetated sediments at the Alcochete site in Tagus (ALC, 0.009 day −1 ). KD varied by a factor of three among sites with highest rates of demethylation observed in non-vegetated sediments in Guadiana (12 ± 1.3 day −1, corresponding to a half-life of 1.4 ± 0.2 h). This study clearly shows that the presence of vegetation in sediments favors the formation of MMHg. Moreover, this effect might be site specific and further studies are needed to confirm the findings reported here. Graphical abstract: Highlights: Use of Hg stable isotopes to determine Hg-methylation/MMHg-demethylation in saltmarsh sediments. Hg-methylation rates were higher in vegetated sediments. MMHg-demethylation rates were in general higher in non-vegetated sediments. Methylmercury daily production in salt-marsh sediments were estimated. Abstract : Higher mercury methylation rates in salt-marsh sediments evidence the effect of plants to create favorable conditions for methylmercury formation.